Logika Matematika Perspektif Nilai-Nilai Moral Berlandaskan Ayat-Ayat Al-Quran Dalam Kehidupan Sehari-Hari - Febiani, Devita Indri; Sa’adah, Nailis; Kholil, Mohammad; Nurdina, Elvi (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2024)
The purpose of this research is to explain how mathematical logic can be used as a tool for understanding and applying moral values ​​contained in the teachings of the Al-Quran in everyday life. This research uses literature review or literature study. Researchers used the bibliographic survey method to collect data to discuss the research title. Relevant data is collected by drawing specific conclusions from general theories. The results of the study show that there are several verses of the Koran that contain mathematical logic from the perspective of moral values, including Al-Insyirah, Al-Fatihah, An-Nisa', and others. The moral values ​​contained in the letter include being honest, persistent or never giving up, obeying the law, and so on.